Heterogeneous Pd catalysts as emulsifiers in Pickering emulsions for integrated multistep synthesis in flow chemistry - Hiebler, Katharina; Lichtenegger, Georg J.; Maier, Manuel C.; Park, Eun Sung; Gonzales-Groom, Renie; Binks, Bernard P.; Gruber-Woelfler, Heidrun (Beilstein Journal of Organic Chemistry, 2018)
Within the “compartmentalised smart factory” approach of the ONE-FLOW project the implementation of different catalysts in “compartments” provided by Pickering emulsions and their application in continuous flow is targeted. We present here the development of heterogeneous Pd catalysts that are ready to be used in combination with biocatalysts for catalytic cascade synthesis of active pharmaceutical ingredients (APIs). In particular, we focus on the application of the catalytic systems for Suzuki–Miyaura cross-coupling reactions, which is the key step in the synthesis of the targeted APIs valsartan and sacubitril. An immobilised enzyme will accomplish the final product formation via hydrolysis. In order to create a large interfacial area for the catalytic reactions and to keep the reagents separated until required, the catalyst particles are used to stabilise Pickering emulsions of oil and water. A set of Ce–Sn–Pd oxides with the molecular formula Ce0.99−xSnxPd0.01O2−δ (x = 0–0.99) has been prepared utilising a simple single-step solution combustion method. The high applicability of the catalysts for different functional groups and their minimal leaching behaviour is demonstrated with various Suzuki–Miyaura cross-coupling reactions in batch as well as in continuous flow employing the so-called “plug & play reactor”. Finally, we demonstrate the use of these particles as the sole emulsifier of oil–water emulsions for a range of oils.
Keywords: compartmentalisation; heterogeneous catalysis; multistep flow chemistry; palladium; Pickering emulsions